Фотоперетворення в плiвках целюлозо-циннамату при опромiненнi поляризованим ультрафiолетовим свiтлом - Kurioz, Yu. I. (Publishing house "Academperiodika", 2018)
Light-induced changes in photosensitive organic polymer ﬁlms based on cellulose cinnamate have been studied. Film specimens illuminated with polarized UV light are found to become anisotropic. The dependence of the birefringence in the polymer ﬁlm on the illumination time is measured, and the diﬀerence between the refractive indices for the extraordinary and ordinary waves is found to have a maximum. The constant and dynamic anisotropy components are found to exist in the ﬁlms under illumination, and they are driven by diﬀerent recording mechanisms. The relaxation process in the ﬁlms after their UV illumination has been switched-oﬀ can be described by an exponential dependence with the characteristic times typical of the cis-trans isomerization. The mechanism of photodimerization is found to be responsible for the existence of a constant anisotropy component.